2020
DOI: 10.3389/fimmu.2020.00956
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomic Nervous System Pulls the Strings to Coordinate Circadian HSC Functions

Abstract: As for many other adult stem cells, the behavior of hematopoietic stem and progenitor cells (HSPCs) is subjected to circadian regulatory patterns. Multiple HSPC functions, such as proliferation, differentiation or trafficking exhibit time-dependent patterns that require a tight coordination to ensure daily blood cell production. The autonomic nervous system, together with circulating hormones, relay circadian signals from the central clock-the suprachiasmatic nucleus in the brain-to synchronize HSC niche physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…In support of the brain/hematopoietic regulatory link hypothesis is some evidence that the nervous system has a role in regulating HSC, HPC, and hematopoiesis [30][31][32], and that dipeptidylpeptidase (DPP)4/CD26 [24,25,[33][34][35][36][37][38][39] is implicated in mobilization of HSC/HPC out from BM to the blood, and also for regulation of cytokine activity [39]. DPP4 can cleave the neurotransmitter Neuropeptide Y (NPY), and recent work has shown that manipulation of endothelial NPY and its receptors alters behavior of HSC and HPC [24,25].…”
Section: Possible Brain -Hematopoiesis Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the brain/hematopoietic regulatory link hypothesis is some evidence that the nervous system has a role in regulating HSC, HPC, and hematopoiesis [30][31][32], and that dipeptidylpeptidase (DPP)4/CD26 [24,25,[33][34][35][36][37][38][39] is implicated in mobilization of HSC/HPC out from BM to the blood, and also for regulation of cytokine activity [39]. DPP4 can cleave the neurotransmitter Neuropeptide Y (NPY), and recent work has shown that manipulation of endothelial NPY and its receptors alters behavior of HSC and HPC [24,25].…”
Section: Possible Brain -Hematopoiesis Linkmentioning
confidence: 99%
“…These cells are important for maintaining/sustaining immunity and fighting cancer/leukemia and pre-cancer/leukemia cells. These mature cells, including platelets are produced by immature subsets of HSC and HPC found and nurtured mainly in BM of newborns and young and old adults through communication between cytokines, chemokines, and the microenvironment, as well as cell-cell interactions [12,13,[30][31][32]. HSC are functionally defined by their capacity to make more of themselves (self-renew) and to differentiate to form HPC and more mature cells.…”
Section: Need For Experimental Evidence For a Brain -Hematopoiesis Linkmentioning
confidence: 99%
“…Many factors can synchronize peripheral clocks, including the autonomic nervous system ( Becker et al, 2019 ; Garcia-Garcia and Mendez-Ferrer, 2020 ), body temperature ( Buhr et al, 2010 ), fasting/feeding cycles ( Wehrens et al, 2017 ; Lewis et al, 2020 ), and cytokines and hormones ( Astiz et al, 2019 ). The autonomic nervous system is influenced by the circadian clock, and some viruses can infect the peripheral and central nervous system ( Koyuncu et al, 2013 ); however, at the present time, there is no evidence for a direct interaction of viruses, clock, and the autonomic nervous system.…”
Section: Circadian Pathways Shape Viral Infectionmentioning
confidence: 99%
“…The influence of the SCN on the autonomic nervous system alters the sensitivity of peripheral tissues to hormones ( Buijs et al, 2006 ). Consequently, the same hormone stimulus may induce different responses dependent on the time of the day ( Becker et al, 2019 ; Garcia-Garcia and Mendez-Ferrer, 2020 ). The importance of the SCN as the main pacemaker becomes evident as transplantation of a functioning SCN reestablishes the circadian rhythm in genetically arrhythmic mice ( Ralph et al, 1990 ; Sujino et al, 2003 ); however, other extracellular cues can independently synchronize peripheral tissues.…”
Section: Introduction: Circadian Rhythms From the Macroscale To The Mmentioning
confidence: 99%
“…The close relationship between CNS, SNS, Parasympathetic Nervous System, bone metabolism and HSC migration, differentiation and self-renewal is illustrated by the important role of the circadian norepinephrine release by SNS nerves which triggers β3 AR and β2 AR expressed by BM mesenchymal cells and osteoblasts in both humans and mice ( Golan et al, 2018 , 2019 ). Cholinergic signaling in the BM via neurons from both the PNS and SNS in tandem with adrenergic signaling derived from the SNS is also reported to contribute to regulate the circadian regulation of CXCL12 expression in the BM ( García-García et al, 2019 ; García-García and Méndez-Ferrer, 2020 ). Likewise, the CNS exerts long range regulation of HSCs.…”
Section: Nho a Favorable Environment For The Development Of Hematopomentioning
confidence: 99%